2011
DOI: 10.1186/1756-9966-30-49
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mesenchymal Stem Cells in Suppression of Hepatocarcinorigenesis in Rats: Possible Role of Wnt Signaling

Abstract: BackgroundThe present study was conducted to evaluate the tumor suppressive effects of bone marrow derived mesenchymal stem cells (MSCs) in an experimental hepatocellular carcinoma (HCC) model in rats and to investigate the possible role of Wnt signaling in hepato-carcinogenesis.MethodsNinety rats were included in the study and were divided equally into: Control group, rats which received MSCs only, rats which received MSCs vehicle only, HCC group induced by diethylnitroseamine (DENA) and CCl4, rats which rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 73 publications
3
24
0
Order By: Relevance
“…At 6 weeks, the DENA-injected rat liver tissues showed dysplastic changes, including disorganized hepatic tissue. These results were consistent with a previous study, in which hepatocarcinogenesis was shown to be induced in rats at 6 weeks following injection with DENA and weekly subcutaneous injection of CCL4 (65). In the present study, DENA injection for 8 weeks resulted in malignant changes of the liver tissues, including disorganized and irregularly arranged hepatocytes.…”
Section: Discussionsupporting
confidence: 93%
“…At 6 weeks, the DENA-injected rat liver tissues showed dysplastic changes, including disorganized hepatic tissue. These results were consistent with a previous study, in which hepatocarcinogenesis was shown to be induced in rats at 6 weeks following injection with DENA and weekly subcutaneous injection of CCL4 (65). In the present study, DENA injection for 8 weeks resulted in malignant changes of the liver tissues, including disorganized and irregularly arranged hepatocytes.…”
Section: Discussionsupporting
confidence: 93%
“…MSCs have also been proved to be a potential solution in severe liver injury such as ischemia-reperfusion injury [23], acute liver failure [24], or hepatocellular carcinoma [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism may be that the BMCs provide cytokines and growth factors in their microenvironment that enhance epithelial cells functions by paracrine mechanisms [40]. BMCs promote tissue renewing and repairing through synergistic down regulation of proinflammatory cytokines and increased production of soluble factors with antioxidant property.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cancer cells may produce proteins that can activate signaling pathways that facilitate and attract BMCs migration to the tumor site. As a result of injury, tissues produce chemokines attracting the circulated BMCs, and can produce circulating microvesicles including RNA, proteins and a variety of signals argument the tumor growth [40]. …”
Section: Discussionmentioning
confidence: 99%